Comprehensive Analyses of the Spatio-Temporal Variation of New-Energy Vehicle Charging Piles in China: A Complex Network Approach - Wang, Maoze; Wu, Fan; Chen, Junhua (Frontiers in Physics, 2021)
This thesis collects data related to EV charging piles in various provinces in China from the National Bureau of Statistics of China and China Electric Vehicle Charging Infrastructure Promotion Alliance, and analyzes present development of EV chargers from the perspective of a complex network, so as to study the features of distribution of EV charging piles from May 2016 to April 2019 and the spatio-temporal variation in different provinces. Then, this thesis transforms time series data of EV charging piles into the complex network by applying visibility graph model, uses several clustering methods to categorize different provinces, and predict future development of EV charging piles in China. Furthermore, the distribution of EV charging piles across time is analyzed based on the combination of national policies and new energy vehicles in the current, so that local governments of different provinces can put forward corresponding policies to develop relevant industries progressively and promote the sustainable development of EV and green energy industry.